Assessment of the risk of developing type 2 diabetes mellitus in patients with gout based on the FINDRISС scale - O. V. Zhelyabina; M. S. Eliseev; M. N. Chikina; T. S. Panevin (Сахарный диабет, 2022)
BACKGROUND: Gout is associated with a high incidence of type 2 diabetes mellitus (T2DM).AIM: To calculate the risk of T2DM on the FINDRISС scale, to assess the sensitivity and specificity of the scale in patients with gout based on the results of prospective follow-up.MATERIALS AND METHODS: A prospective single-center study included 444 patients with gout over 18 years of age (49 women, 395 men) without diabetes. The duration of follow-up ranged from 2 to 8 years. Initially, the risk of developing diabetes mellitus 2 was calculated according to the Russian version of the FINDRISС scale. The risk of developing T2DM was assessed as «low» with a total score (CC) <7 points, slightly increased — from 7 to 11 points, moderate — from 12 to 14 points, high — from 15 to 20 points, and very high — ≥20 points. To assess the validity of using the FINDRISС scale, an analysis of sensitivity, specificity, construction of the ROC curve with the determination of the area under the curve was carried out. The presence and number of subcutaneous tophi, the number of arthritis attacks over the last year, the number of affected joints during the illness, serum levels of creatinine, uric acid, hs-CRP, glycated hemoglobin were determined.RESULTS: Over 5.66 [2.69; 7.64] years of follow-up, T2DM developed in 108 patients (24.3%). On the FINDRISС scale, low risk was found in 16 (4%), slightly increased in 187 (42%), moderate in 98 (22%), high in 80 (18%), very high in 63 (14%). The most common risk factors (RF) for T2DM included in FINDRISС were BMI> 25 kg / m2  — 85.6% of patients, taking antihypertensive drugs — 81.3% of patients, age over 45 years in 70.5% of patients. The sensitivity and specificity of the FINDRISС scale were 52.8% and 66.3%, respectively. According to these data, the quality of the model was assessed as moderate. 9% vs 31.1% (p = 0.014)), serum MK level ≤300 μmol / L. Developed type 2 diabetes 33.3% of patients with moderate / high / very high risk 18.1% of patients with low or slightly increased risk (p = 0.0002).CONCLUSION: The FINDRISС scale can have sufficient sensitivity (52.8%) and specificity (66.3%) and can be used to calculate the risk of T2DM in patients with gout.